2012
DOI: 10.1002/iub.1025
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of lamivudine, lopinavir, ritonavir, and zidovudine concentration in plasma of HIV‐infected patients by HPLC‐MS/MS

Abstract: SummaryThe nucleoside reverse transcriptase inhibitors lamivudine and zidovudine and the protease inhibitors lopinavir and ritonavir are currently used in anti-human immunodeficiency virus (HIV) therapy. Here, a high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS) method, using a hybrid quadrupole time-of-flight mass analyzer, is reported for the simultaneous quantification of lamivudine, lopinavir, ritonavir, and zidovudine in plasma of HIV-infected patients. The volume of plasma sample was 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…The literature is lacking in studies involving the use of MIP for extraction of ARVs from human plasma. A typical comparison with other methods reported in the literature using SPE for the determination of 3TC, AZT and EFZ in different matrices is presented in Supporting Information Table 3 , which confirm that LOQ value is appropriate and comparable with other research works. The low LOQs are mainly attributed to the use of highly sensitive, complex and expensive detector, i.e.…”
Section: Resultssupporting
confidence: 83%
“…The literature is lacking in studies involving the use of MIP for extraction of ARVs from human plasma. A typical comparison with other methods reported in the literature using SPE for the determination of 3TC, AZT and EFZ in different matrices is presented in Supporting Information Table 3 , which confirm that LOQ value is appropriate and comparable with other research works. The low LOQs are mainly attributed to the use of highly sensitive, complex and expensive detector, i.e.…”
Section: Resultssupporting
confidence: 83%
“…A hydrophobically modified 3TC derivative (designated M3TC) was synthesized according to the scheme illustrated in Figure 1 and described in the Supplemental Digital Content, 31 http://links.lww.com/QAI/A900 . M3TC nanoparticles were formulated by high-pressure homogenization (Avestin EmulsiFlex-C3; Avestin Inc., Ottawa, ON, Canada), using P407 and folate-decorated P407 (FA-P407) to encase the drug crystals.…”
Section: Methodsmentioning
confidence: 99%
“…This RP-HPLC assay allows simultaneous quantification of six PIs [IDV, RTV, SQV, NFV, APV, and LPV] using carbamazepine as an internal standard. Thereafter, several simultaneous assays on HPLC with UV PDA, Diode array and MS detectors have been made available in the literature [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215][216]. Although not much in use, Azoulay et al in 2004 reported an immunoassay for LPV [217].…”
Section: Lopinavirmentioning
confidence: 99%